Biomarkers of hemorrhagic transformation of acute ischemic stroke – A cross-sectional study - Subhashini K.; Devipriya Surapaneni; Jagadeesan M. (Romanian Medical Journal)
Background. Hemorrhagic transformation (HT) is a serious complication that can arise in individuals experiencing acute ischemic stroke (AIS), whether it occurs spontaneously or following thrombolytic therapy, resulting in considerable morbidity and mortality. Hemorrhagic changes are associated with several risk factors, including excessive blood sugar levels, hypertension, the severity of a stroke, and reperfusion. Aim. To assess the commonly available blood parameters such as lipid profile, serum magnesium, and serum ferritin as tools to identify patients who are at risk of hemorrhagic transformation after an acute ischemic stroke. Materials and methods. The study was conducted at the Saveetha Medical College, Chennai, Tamil Nadu, in India, as a cross-sectional study, and a total of 142 patients diagnosed with acute ischemic stroke were enrolled for this study from January 2023 to January 2024. Results. Among the 32 patients who had a hemorrhagic transformation, all 32 (100%) patients had elevated serum ferritin levels and the remaining 110 patients who had no hemorrhagic transformation were found to have normal serum ferritin levels and the difference was statically significant (p<0.001). Total cholesterol, serum LDL, serum HDL, and serum triglycerides had no statistically significant association with hemorrhagic transformation among the patients. Conclusion. The present study concludes that people with lower serum magnesium on admission and higher serum ferritin were found to be at risk. Serum lipid profile had no statistically significant association with hemorrhagic transformation among the patients.